Atypical Porcine Pestivirus Molecular Evolution within a Persistently Infected Swine Farm - Alba Folgueiras-González; Robin van den Braak; Bartjan Simmelink; Martin Deijs; Ad de Groof; Lia van der Hoek (Proceedings, 2020)
Atypical porcine pestivirus (APPV) is a single stranded RNA virus from the family Flaviviridae. [...]